The role of personality traits in business intentions among active women entrepreneurs - Luong V. Q. Duy (International Studies of Economics)
Abstract Entrepreneurs and entrepreneurship are important for economic growth and development. Yet insufficient attention has been paid to psychological characteristics such as personality characteristics as factors for women entrepreneurship in emerging economies. This study aims to investigate the associations between women entrepreneurs' business intentions and their personality traits. This study utilizes binomial logistic regression for hypothesis testing using the unique data set from a survey of small and medium manufacturing enterprises located in nine cities and provinces from three main geographical regions of Vietnam. The findings show that personality factors can be important for women entrepreneurs' business intentions. Unlike some other studies, the personality trait conscientiousness is found negatively correlated with women's entrepreneurial intentions. External factors such as local institutional quality and business networks have been found to stimulate women entrepreneurial intentions. The finding also raises concerns over the undergraduate training programs that need to be improved to make future students more confident in planning their business intentions if entrepreneurship is their career choice. The findings provide a key contribution to the existing literature of entrepreneurship in the context of an emerging economy where studies on women's entrepreneurship are scarce.